1984
DOI: 10.1002/mpo.2950120305
|View full text |Cite
|
Sign up to set email alerts
|

Lithium treatment in adults with acute myeloid leukemia receiving chemotherapy

Abstract: To determine whether lithium can shorten chemotherapy-induced neutropenia, 35 adult patients with newly diagnosed acute myeloid leukemia undergoing initial chemotherapy were randomized either to receive oral lithium started at the time of biopsy-proven hypoplasia or to receive no lithium. This study failed to show statistically significant shortening of the duration of chemotherapy-induced neutropenia in the lithium treatment group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1987
1987
1989
1989

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…This change was associated with a reduction in the number of infective episodes. Belch et al (198 1) reporting on a randomized trial of 73 patients found lithium to be ineffective in reducing the period of neutropenia as did Horns et al (1984) in a trial of 35 patients. In a preliminary study Stein et al (1979) showed promising results but these were not confirmed in a larger randomized control trial (Stein et al, 1984).…”
Section: Discussionmentioning
confidence: 93%
“…This change was associated with a reduction in the number of infective episodes. Belch et al (198 1) reporting on a randomized trial of 73 patients found lithium to be ineffective in reducing the period of neutropenia as did Horns et al (1984) in a trial of 35 patients. In a preliminary study Stein et al (1979) showed promising results but these were not confirmed in a larger randomized control trial (Stein et al, 1984).…”
Section: Discussionmentioning
confidence: 93%
“…In addition, lithium is used in the treatment of leukopenia, for example, after systemic chemotherapy, as it has been shown to cause leukocytosis via a selective increase in the number of circulating neutrophils (reviewed by Leber [249] ). Although such an effect has been shown in cancer patients by several researchers; for example, in the treatment of small cell carcinoma of the lung [250], it is not observed by others, as in the case of acute myeloid leukemia therapy [251,252].…”
Section: Lithiummentioning
confidence: 99%